Characterization of the Micro‐Morphology and Compositional Distribution of Chang'e‐5 Lunar Soil Mineral Surfaces Using TOF‐SIMS - Tinglu Song; Jie Liu; Chunlin Zhang; Xinyu Yang; Taiyang Chen; Shunzi Jiang; Fan Xu; Ning Li; Menghua Zhu; Shaolin Li; Meishuai Zou (Advanced Science)
Abstract The lunar soil samples returned by China's Chang'e‐5 (CE‐5) contain valuable information on geological evolutions on the Moon. Herein, by employing high‐resolution time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS), five rock chip samples from the CE‐5 lunar soil are characterized in‐depth, which reveal micro‐morphological and compositional features. From the elemental/molecular ion distribution images, minerals such as pyroxene, ilmenite, feldspar, K‐rich glass, silica, and silicate minerals are identified, along with their occurrence states and distribution results. More importantly, uncommon vesicle‐like patterns are probed via TOF‐SIMS, which may not be captured by conventional electron microscopy. The possible origins of vesicles are also proposed. Hopefully, these discoveries will provide essential guidance for future investigations on the Moon and accelerate the application of TOF‐SIMS in space exploration.